Daunorubicin reduces MBNL1 sequestration caused by CUG-repeat expansion and rescues cardiac dysfunctions in a Drosophila model of myotonic dystrophy - Mouli Chakraborty; Chantal Sellier; Michel Ney; Villa Pascal; Nicolas Charlet-Berguerand; Ruben Artero; Beatriz Llamusi (The Company of Biologists, 2018)
Myotonic dystrophy (DM) is a dominantly inherited neuromuscular disorder caused by expression of mutant myotonin-protein kinase (DMPK) transcripts containing expanded CUG repeats. Pathogenic DMPK RNA sequesters the muscleblind-like (MBNL) proteins, causing alterations in metabolism of various RNAs. Cardiac dysfunction represents the second most common cause of death in DM type 1 (DM1) patients. However, the contribution of MBNL sequestration in DM1 cardiac dysfunction is unclear. We overexpressed Muscleblind (Mbl), the Drosophila MBNL orthologue, in cardiomyocytes of DM1 model flies and observed a rescue of heart dysfunctions, which are characteristic of these model flies and resemble cardiac defects observed in patients. We also identified a drug - daunorubicin hydrochloride - that directly binds to CUG repeats and alleviates Mbl sequestration in Drosophila DM1 cardiomyocytes, resulting in mis-splicing rescue and cardiac function recovery. These results demonstrate the relevance of Mbl sequestration caused by expanded-CUG-repeat RNA in cardiac dysfunctions in DM1, and highlight the potential of strategies aimed at inhibiting this protein-RNA interaction to recover normal cardiac function.